NIMG-33. CHANGES IN MAGNETIC RESONANCE IMAGING AFTER PROTON BOOST THERAPY FOR GLIOBLASTOMA WITH AND WITHOUT TUMOR TREATING FIELDS THERAPY. (9th November 2020) - Goett, Hanna; Jensen, Alexandra; Struffert, Tobias; Uhl, Eberhard; Stein, Marco
Abstract: BACKGROUND: Tumor treating fields (TTFields) are an approved glioblastoma (GBM) treatment modality that demonstrated a significant improved median overall survival in newly diagnosed GBM patients. Data about morphologic changes in serial magnetic resonance imaging (MRI) for patients with a combination therapy of TTFields and proton boost therapy does not exist. METHODS: Twenty-two patients were included in this study. All patients were treated with initial tumor resection followed by combined chemo- and radiation therapy. Radiation therapy was performed with 50.0 Gy photons and a proton boost with 10 Gy equivalent (Gy(RBE)). 11 patients were additionally treated with TTFields. RESULTS: A new increase in contrast enhancement and/or a progress in the T2 FLAIR hyperintensity was observed in 54.5% (N=12) at 3 months and in 31.8% (N=7) at 6 months. No differences were observed between patients with and without TTFields therapy at 3 months [63.6% (N=7) vs. 45.5% (N=5); P=0.392] and at 6 months [27.3 (N=3) vs. 36.3% (N=4); P=0.647). By the RANO criteria a progressive disease (PD) was observed in 6 patients (27.3%) at 3 months and in 7 patients (31.8%) at 6 months. Pseudoprogression (PP) was observed in in 36.4% (N=8) at months and in 27.3% (N=6) at 6 months. Neither for PD at 3 months [36.4% (N=4) vs. 18.2% (N=2); P=0.338] or at 6 months [36.4% (N=4) vs. 27.3% (N=3); P=0.647), nor for PP at 3 months [45.5% (N=5) vs. 27.2% (N=3); P=0.375] or at 6 months [18.2% (N=2) vs. 36.4% (N=4); P=0.338] differences for patients with and without TTFields therapy were found. CONCLUSION: Increased contrast enhancement and/or increased T2 FLAIR MRI hyperintensity after proton boost therapy are common. Furthermore, the rates for new contrast enhancement, PD, and PP after photon therapy with and without additional TTFields therapy are comparable.